2020
DOI: 10.3390/molecules25132982
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Partial Acid Hydrolysis on Size, Dispersity, Monosaccharide Composition, and Conformation of Linearly-Branched Water-Soluble Polysaccharides

Abstract: The effect of partial acid hydrolysis on the physical and chemical properties of galactomannan, arabinoxylan, and xyloglucan was investigated. Polysaccharides were treated at 50 °C with hydrochloric acid for 3–48 h. Portions of isopropanol (i-PrOH) were added sequentially to the hydrolyzates, resulting in fractions that were collected by centrifugation. As expected, a significant reduction of weight-average molecular weight (Mw) was observed with increasing hydrolysis time. Fractional precipitation was success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…The commercial standards of neutral dietary fibers were purchased from Megazyme (Bray, Ireland): barley β-glucan (BG) (low viscosity, Lot 100401, Mw 179 kDa, ~95 % purity); wheat arabinoxylan (AX) (medium viscosity, Lot 40601a, Mw 323 kDa, Ara: Xyl = 38/ 62, ~95 % purity); guar galactomannan (GM) (high viscosity, Lot 100301c, Mw 380 kDa, Gal: Man = 38/62). The Mw of GM reported in this work is nearly 4 times higher than reported by Megazyme in the technical data, which was also found in other works (Lupo et al, 2020;Robinson et al, 1982;Tayal et al, 1999). The stable free radical, 4-carboxy-2,2,6,6-tetramethylpiperidinyloxy (4-carboxy-TEMPO), 4-amino-2,2,6,6-tetramethylpiperidinyloxy (4-amino-TEMPO) were purchased from Sigma-Aldrich (St. Louis, MO, United States) and used without further purification.…”
Section: Methodssupporting
confidence: 88%
“…The commercial standards of neutral dietary fibers were purchased from Megazyme (Bray, Ireland): barley β-glucan (BG) (low viscosity, Lot 100401, Mw 179 kDa, ~95 % purity); wheat arabinoxylan (AX) (medium viscosity, Lot 40601a, Mw 323 kDa, Ara: Xyl = 38/ 62, ~95 % purity); guar galactomannan (GM) (high viscosity, Lot 100301c, Mw 380 kDa, Gal: Man = 38/62). The Mw of GM reported in this work is nearly 4 times higher than reported by Megazyme in the technical data, which was also found in other works (Lupo et al, 2020;Robinson et al, 1982;Tayal et al, 1999). The stable free radical, 4-carboxy-2,2,6,6-tetramethylpiperidinyloxy (4-carboxy-TEMPO), 4-amino-2,2,6,6-tetramethylpiperidinyloxy (4-amino-TEMPO) were purchased from Sigma-Aldrich (St. Louis, MO, United States) and used without further purification.…”
Section: Methodssupporting
confidence: 88%
“…Similarly, for pB1AS plasmids, in three of the four commercial minipreps, the endotoxin levels were about half of those determined for pmaxGFP and considerably higher than detected for FPI minipreps (206-350 EU/μg and 5 EU/μg, respectively; Table 1 & Supplementary Figure 4). The low level of endotoxin observed for the FPI method is consistent with the removal of most of the endotoxins by extraction (or precipitation) with isopropanol [12,13]. Fourth, the quality of pmaxGFP and pB1AS was tested in transfection experiments.…”
mentioning
confidence: 64%
“…However, we cannot exclude that, in vivo , the upper digestive tract passage may impact the AX extracts and their consecutive colonic fermentation. For instance, it was demonstrated that hydrochloric acid treatments lead to the degradation of arabinose substitutions within the AX chains ( 36 ). Therefore, future in vitro studies could investigate if processing-induced changes in soluble AX and their prebiotic potential are preserved after upper digestive tract conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The fermentation of various soluble WBAX and RFAX by colon microbiota was determined by an in vitro colon high-throughput batch fermentation using two different in vitro cultivated proximal colon microbiota (CM 1 and CM 2). The focus of this study was on the impact of processing-induced structural changes of AX on its colonic fermentation; therefore, the hydrochloric acid predigestion of extracts prior to the fermentation was not performed as it may have additionally modified the structure of AX, preventing the direct processing-structure-function correlation ( 36 ). The microbiota were derived from two independent stable PolyFermS systems, a continuous colon fermentation model, which were inoculated with the immobilized fecal microbiota of healthy human adults and are designed to continuously cultivate the proximal colon microbiota akin to donor profile ( 37 , 38 ).…”
Section: Methodsmentioning
confidence: 99%